Glial scarring around intra-cortical MEA implants with flexible and free microwires inserted using biodegradable PLGA needles - Darlot, Fannie; Villard, Paul; Salam, Lara Abdel; Rousseau, Lionel; Piret, Gaëlle (Frontiers in Bioengineering and Biotechnology, 2024)
A lot of invasive and non invasive neurotechnologies are being developed to help treat neurological pathologies and disorders. Making a brain implant safe, stable, and efficient on the long run is one of the requirements to abide to neuroethics and overcome limitations for numerous promising neural treatments. A main limitation is their low biocompatibility, characterized by the damage they create to the brain tissue and their low adhesion to it, this being partly linked to frictions maintained overtime by the mechanical mismatch between the soft brain tissue and their more rigid wires. Here, we performed a short biocompatibility assessment of bio-inspired intra-cortical implants named "Neurosnooper" made of a Micro Electrode Array with microwires being free between them, therefore mimicking axons, and consisting of a thin flexible polymer-metal-polymer stacking. Implants were assembled to Poly-Lactic-Glycolic-Acid (PLGA) biodegradable needles to proceed to their intracortical implantation. The study of glial scars around implants, at seven days and two months postimplantation, revealed a good adhesion between the brain tissue and implant wires, and a low glial scar thickness. The lowest corresponds to electrode wires with a section size of 8 x 10 µm, compared to implants with the 8 x 50 µm electrode wire section size, and a straight shape seems better than a zig zag. Therefore, in addition to flexibility, size and shape parameters are important when designing electrode wires of the next clinical intra-cortical implant generation.